Ultrahigh magnetic field study of layer split bands in graphite. - Nicholas, R; Solane, P; Portugall, O (2013)
We report studies of the magnetospectroscopy of graphite into a new regime of high energies and ultrahigh magnetic fields which allows us to perform the first spectroscopic studies of the interlayer split-off bands, E1 and E2. These bands can be well described by an asymmetric bilayer model and have only a small interlayer band gap asymmetry. We show that all of the properties of the electrons and holes can be described by a simple relativistic behavior determined by γ0 and γ1.